KADAR HORMON FSH BASAL SEBAGAI PREDIKTOR KEBERHASILAN STIMULASI OVARIUM PADA PROGRAM BAYI TABUNG - , Sandri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Infertility was a common problem of married couples, the prevalence was approximately 9%. This occured both in developing countries as well as those already developed. Approximately 56% of the actual needed of assistance in the field of medicine but in reality only 22% who get it, Follicular development was inseparable from the Follicle Stimulating Hormone (FSH), in addition to other hormones (LH) resulting in an increase in the hormone estrogen. IVF success was influenced among others by causing-- infertility, age, endometrial, number of embryos transferred, embryo quality. IVF methods one of which stimulates the ovaries. Ovarian response will be assessed by the number of mature follicles Objective: Analyzing goals basal FSH levels as a predictor of the number of developing follicles in IVF-ICSI program Materials and Methods: A retrospective cohort study, all patients who came to the Permata Hati Infertility Clinic in Dr. Sardjito Hospital IVF-ICSI program. Data retrieved from the medical records of patients from January 2010 to December 2012. Inclusion criteria, women following IVF-ICSI with ovarian stimulation in Permata Hati Hospital Infertility Clinic in Dr Sardjito Hospital. Results: The number 67 subjects research showed 34 mature follicles with basal FSH â¤ 7.5 mIU / mL, these resulted significant difference compared with FSH > 7.5 mIU / mL, RR 1.48, p 0.035 ( 95% CI 1.238 -1.949). Conclusion: This study suggests that a low basal FSH would result in more of the mature follicles